(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Background: Hygiene refers to conditions and practices that helps maintain health and prevent the spread of diseases. Whereas in popular culture and parlance it can often mean mere “cleanliness,” hygiene in its fullest and original meaning goes much beyond that to include all circumstances and practices, lifestyle issues, premises and commodities that engender a safe and healthy environment. The aim of this study is to assess the knowledge and practice of nurses regarding hygiene in the care of comatose patient in a Government Hospital in Jordan. Materials and methods: The study was conducted during the period of 1 st June 2016 to 1st December 2016. The design of this study is Descriptive cross – sectional hospital base analysis by manual analysis method. This is a type of study in which a condition and potentially related factors are being measured at a specific point in time for a defined population (NEDARC, 2016). Results: The study respondents were fifty (50) nurses, among these respondents, twenty six (26) were males and twenty four (24) were females which was ethically informed to participate in this study. The study showed that knowledge of nurses about hygiene in the care of comatose patient were 45% good, 40.1% poor knowledge and 14.9% moderate knowledge. Conclusion: The present study concluded that study sample has a moderate to good knowledge. Based on the study findings it is recommended that the nurses needs to attend courses and trainings about hygiene of comatose patient to improve their practice.